Graviton propagator, renormalization scale and black-hole like states - X. Calmet; R. Casadio; A.Yu. Kamenshchik; O.V. Teryaev (Physics Letters B, 2017)
We study the analytic structure of the resummed graviton propagator, inspired by the possible existence of black hole precursors in its spectrum. We find an infinite number of poles with positive mass, but both positive and negative effective width, and studied their asymptotic behaviour in the infinite sheet Riemann surface. We find that the stability of these precursors depend crucially on the value of the normalisation point scale.